Kontekstualitas Pemahaman Hadis-Hadis tentang Perang Melalui Pendekatan Historis - Adi Abdullah Muslim (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
The phenomenon that there are several community who think that Islam teaches violence and war is one form of error in understanding hadiths that speak in the context of war. The shallowness in understanding hadith accompanied by the ease of receiving information without accompanying clarification has created a local uproar regarding people's discomfort in interacting with people studying religion. This understanding will change when they can see the same hadith discussing one theme. This method is used as the approach used in this research. Understanding hadith through a compromising approach (al-jam'u) and a historical approach to the analysis. Meanwhile, the primary sources used are two al-Sahih books, al-Jami' al-Sahih li Imam al-Bukhari and al-Jami' al-Sahih li Imam Muslim as well as additional books from Sunan Abu Daud and Sunan Imam al-Tirmidhi. The nature of the research used is a description of critical analysis with a socio-historical approach. Keyword: understanding, contextual, hadith, war,